Rasio lebar mesiodistal gigi Bolton pada geligi berjejal dan geligi normal - Susilowati Susilowati; Meryl Dekaria (DiscoverSys Inc., 2007)
The orthodontic â€œfinishingâ€ phase is recognized for the many details to accomplish anexcellent result. A high percentage of finishing-phase difficulties arise because of toothsize imbalance that could have been considered during the initial diagnosis and treatmentplanning. The aim of this study was to determine whether the Bolton's analysis appliesfor the crowded and non crowded dentitions. This study involved 60 subjects (30crowded and 30 non-crowded; 29 males and 31 females). Criteria for sample selectioncomprised absence of interproximal caries/filling, no residual crown-bridge restoration,no tooth deformity, aged over 17 years, never undergone orthodontic treatment, and thepresence of teeth from right first molar through left first molar, both upper and lower.Tooth size measurements were performed on study models. The statistical analysis usedwere descriptive and t-test. The results of the study were as follows: the mesiodistal toothwidths on males were bigger that those on females, the mesiodistal tooth widths oncrowded group were bigger than those on normal group but the difference wasinsignificant statistically (p>0.05); anterior ratio in crowded group was smaller that thatin normal group; overall ratio in crowded group was bigger than that in normal group butthe difference was insignificant (p>0.05). Anterior ratio of the two groups was biggerthan Anterior Bolton Mean, it means that the discrepancy was present on the lower arch.Overall ratio of the two groups was smaller than Overall Bolton Mean, it means that thediscrepancy was present on the upper arch.